APOE ε2 is associated with increased tau pathology in primary tauopathy. Issue 1 (December 2018) - Zhao, Na; Liu, Chia-Chen; Ingelgom, Alexandra; Linares, Cynthia; Kurti, Aishe; Knight, Joshua; Heckman, Michael; Diehl, Nancy; Shinohara, Mitsuru; Martens, Yuka; Attrebi, Olivia; Petrucelli, Leonard; et al.
Abstract Apolipoprotein E (APOE ) ε4 allele is the strongest genetic risk factor for late-onset Alzheimer's disease mainly by modulating amyloid-β pathology.APOE ε4 is also shown to exacerbate neurodegeneration and neuroinflammation in a tau transgenic mouse model. To further evaluate the association ofAPOE genotype with the presence and severity of tau pathology, we express human tau via an adeno-associated virus gene delivery approach in humanAPOE targeted replacement mice. We find increased hyperphosphorylated tau species, tau aggregates, and behavioral abnormalities in mice expressingAPOE ε2/ε2. We also show that in humans, theAPOE ε2 allele is associated with increased tau pathology in the brains of progressive supranuclear palsy (PSP) cases. Finally, we identify an association between theAPOE ε2/ε2 genotype and risk of tauopathies using two series of pathologically-confirmed cases of PSP and corticobasal degeneration. Our data together suggestAPOE ε2 status may influence the risk and progression of tauopathy. TheAPOE ε4 allele is a strong genetic risk factor for Alzheimer's disease, whereas theAPOE ε2 allele is protective. Here the authors show that mice expressing the humanAPOE ε2/ε2 genotype have increased tau pathology and related behavioral deficits; they also find that theAPOE ε2 allele is associated with an increased burden of tau pathology in postmortem human brains with progressive supranuclear palsy.